Impact of Torque on Assessment of Syndesmotic Injuries Using Weightbearing Computed Tomography Scans. (June 2019) - Krähenbühl, Nicola; Bailey, Travis L.; Weinberg, Maxwell W.; Davidson, Nathan P.; Hintermann, Beat; Presson, Angela P.; Allen, Chelsea McCarty; Henninger, Heath B.; Saltzman, Charles L.; Barg, Alexej
Background: The diagnosis of subtle injuries to the distal tibiofibular syndesmosis remains elusive. Conventional radiographs miss a large subset of injuries that present without frank diastasis. This study evaluated the impact of torque application on the assessment of syndesmotic injuries when using weightbearing computed tomography (CT) scans. Methods: Seven pairs of male cadavers (tibia plateau to toe-tip) were included. CT scans with axial load application (85 kg) and with (10 Nm) or without torque to the tibia (corresponding to external rotation of the foot and ankle) were taken during 4 test conditions. First, intact ankles (native) were scanned. Second, 1 specimen from each pair underwent anterior inferior tibiofibular ligament (AITFL) transection (condition 1A), while the contralateral underwent deltoid transection (condition 1B). Third, the lesions were reversed on the same specimens and the remaining intact deltoid or AITFL was transected (condition 2). Finally, the distal tibiofibular interosseous membrane (IOM) was transected in all ankles (condition 3). Measurements were performed to assess the integrity of the distal tibiofibular syndesmosis on digitally reconstructed radiographs (DRRs) and on axial CT scans. Results: Torque impacted DRR and axial CT scan measurements in almost all conditions. The ability to diagnose syndesmotic injuries using axial CT measurements improved when torque was applied. No significant syndesmotic morphological change was observed with or without torque for either isolated AITFL or deltoid ligament transection. Discussion: Torque application had a notable impact on two-dimensional (2-D) measurements used to diagnose syndesmotic injuries for both DRRs and axial CT scans. Because weightbearing conditions allow for standardized positioning of the foot while radiographs or CT scans are taken, the combination of axial load and torque application may be desirable. Clinical Relevance: Application of torque to the tibia impacts 2-D measurements and may be useful when diagnosing syndesmotic injuries by DRRs or axial CT images.